A atuação da Diocese de Santo André durante a Ditadura Civil-Militar nos episcopados de Dom Jorge Marcos de Oliveira e Dom Cláudio Hummes (1964 – 1980) - Servo, Cleonice Rosa do Nascimento (2016)
This paper explore some issues experienced within the Roman Catholic Diocese of Santo André, located in the region known as the largest industrial park of Latin America, ABC Paulista, at the metropolitan area of the city of Sao Paulo, between 1964 and 1980, period of Civil-Military Dictatorship in Brazil. For this analysis, we considered social initiatives discussed, above all, from the Second Vatican Council, and with more vehemence, in Latin America, in the meetings of the Episcopal Conferences of Medellin, 1968, and Puebla, 1979. Based on actions promoted by Don Jorge Marcos de Oliveira and Don Claudio Hummes, we have tried to go through important historical moments about the struggle of the workers of the region and the support offered by the Catholic Church, through its movements, in a period of economic recession, social problems, political repression and intolerance by the Brazilian State. To understand this context, we get support on historical and critical reading about the period, documents that retains vestiges of that time, subject who lived their experiences that time and pastoral guidance documents from the Catholic Church The Don Jorge Marcos de Oliveira and Don Claudio Hummes initiatives influenced the actions of the working class in ABC Paulista and participated in the process of reorganization of labor unions in the late 1970’s, resulting in big strike movements that, therefore, reflected in the process of political opening